Physical Therapy for Neurological Conditions in Geriatric Populations - Carmeli, Eli (Frontiers in Public Health, 2017)
With more of the world’s population surviving longer, individuals often face age-related neurology disorders and decline of function that can affect lifestyle and well-being. Despite neurophysiological changes affecting the brain function and structure, the aged brain, in some degree, can learn and relearn due to neuroplasticity. Recent advances in rehabilitation techniques have produced better functional outcomes in age-related neurological conditions. Physical therapy (PT) of the elderly individual focuses in particular on sensory–motor impairments, postural control coordination, and prevention of sarcopenia. Geriatric PT has a significant influence on quality of life, independent living, and life expectancy. However, in many developed and developing countries, the profession of PT is underfunded and understaffed. This article provides a brief overview on (a) age-related disease of central nervous system and (b) the principles, approaches, and doctrines of motor skill learning and point out the most common treatment models that PTs use for neurological patients.